The potential of dibenzazepine carboxamides in cancer therapy - Afsordeh, Nastaran; Pournajaf, Safura; Mirnajafi-Zadeh, Javad; Pourgholami, Mohammad Hossein (Frontiers in Pharmacology, 2025)
Cancer is a leading cause of mortality worldwide, with most conventional treatments lacking efficacy and having significant challenges like drug resistance. Finding new molecules is quite challenging in terms of cost, time and setbacks. Hence, drug repurposing is considered sensible for skipping the long process of drug development. Dibenzazepine carboxamides, as traditional anticonvulsants, primarily function by blocking voltage-gated sodium channels, which not only mitigate seizures but also influence mood disorders through modulation of serotonin and dopamine. Recent studies have uncovered their anticancer properties, demonstrated by both in vitro and in vivo experiments. This review comprehensively examines dibenzazepine’s pharmacodynamics, pharmacokinetics, and clinical applications, focusing on their emerging role in oncology. By highlighting the anticancer mechanisms of action—including apoptosis induction, inhibition of HDAC, Wnt/β-Catenin signaling, and Voltage-gated sodium channels, we suggest further research to fully elucidate their therapeutic potential and application in cancer treatment.